2003
DOI: 10.1038/sj.onc.1206256
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ErbB3–PI3-kinase pathway is correlated with malignant phenotypes of adenocarcinomas

Abstract: Signet-ring cell carcinomas are malignant dedifferentiated carcinomas, which are frequently found in the stomach. We previously demonstrated that a 200 kDa protein is often constitutively phosphorylated on tyrosine and bound to phosphatidylinositol 3-kinase (PI3-kinase) in signetring cell carcinoma cells. In this study, we purified the 200 kDa protein from an extract of NUGC-4 cells, a cell line of signet-ring cell carcinoma, and identified it as ErbB3. ErbB3 was found to be phosphorylated selectively in dedif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…2B). Other studies have shown that LY294002 down-regulates MUC1 in gastric carcinoma cells (36). By contrast, LY294002 had no apparent effect on MUC1 expression in 3Y1/MUC1 cells, indicating that MUC1 is regulated by PI3K-independent pathways (Fig.…”
Section: Muc1mentioning
confidence: 72%
See 1 more Smart Citation
“…2B). Other studies have shown that LY294002 down-regulates MUC1 in gastric carcinoma cells (36). By contrast, LY294002 had no apparent effect on MUC1 expression in 3Y1/MUC1 cells, indicating that MUC1 is regulated by PI3K-independent pathways (Fig.…”
Section: Muc1mentioning
confidence: 72%
“…Activates the PI3K/Akt Pathway-PI3K is aberrantly activated in diverse human carcinomas (1,11,36). Interaction of the PI3K p85 subunit with phosphotyrosine residues of activated growth factor receptors or adaptor proteins results in stimulation of the PI3K p110 catalytic subunit.…”
Section: Muc1mentioning
confidence: 99%
“…343 Strong evidence for a key role for ERBB3 in gastric malignancy came from a study of poorly differentiated signet-ring cell gastric carcinomas. 344 Activation of ERBB3 and complexation with PI3K were associated with the de-differentiated state; expression of a chimera of activated ERBB2/ERBB3 resulted in increased malignancy of an initially highly differentiated cell line.…”
Section: Melanomasmentioning
confidence: 99%
“…Recently, we found that PI 3-kinase was often activated by binding to ErbB3 in signet-ring cell lines (Kobayashi et al, 2003). In these cells, ErbB2 was activated as well, suggesting that the ErbB2/ErbB3 complex may play a role in the formation of signet-ring cell carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…In these cells, ErbB2 was activated as well, suggesting that the ErbB2/ErbB3 complex may play a role in the formation of signet-ring cell carcinomas. Introduction of constitutively active ErbB3 in a differentiated adenocarcinoma cell line, HCC2998, resulted in loss of cell-cell contact and high expression of mucin (MUC1), a marker of malignant tumors (Yonezawa and Sato, 1997;Kobayashi et al, 2003). However, the function of the downstream molecules of PI 3-kinase in the formation of signet-ring cell carcinoma remains elusive.…”
Section: Introductionmentioning
confidence: 99%